Maternal Protein Restriction Alters the Expression of Proteins Related to the Structure and Functioning of the Rat Offspring Epididymis in an Age-Dependent Manner - Cavariani, Marilia Martins; de Mello Santos, Talita; Chuffa, Luiz Gustavo de Almeida; Pinheiro, Patrícia Fernanda Felipe; Scarano, Wellerson Rodrigo; Domeniconi, Raquel Fantin (Frontiers in Cell and Developmental Biology, 2022)
Nutrition is an environmental factor able to activate physiological interactions between fetus and mother. Maternal protein restriction is able to alter sperm parameters associated with epididymal functions. Since correct development and functioning of the epididymides are fundamental for mammalian reproductive success, this study investigated the effects of maternal protein restriction on epididymal morphology and morphometry in rat offspring as well as on the expression of Src, Cldn-1, AR, ER, aromatase p450 and 5α-reductase in different stages of postnatal epididymal development. For this purpose, pregnant females were allocated to normal-protein (NP – 17% protein) and low-protein (LP – 6% protein) groups that received specific diets during gestation and lactation. After weaning, male offspring was provided only normal-protein diet until the ages of 21, 44 and 120 days, when they were euthanized and their epididymides collected. Maternal protein restriction decreased genital organs weight as well as crown-rump length and anogenital distance at all ages. Although the low-protein diet did not change the integrity of the epididymal epithelium, we observed decreases in tubular diameter, epithelial height and luminal diameter of the epididymal duct in 21-day-old LP animals. The maternal low-protein diet changed AR, ERα, ERβ, Src 416 and Src 527 expression in offspring epididymides in an age-dependent manner. Finally, maternal protein restriction increased Cldn-1 expression throughout the epididymides at all analyzed ages. Although some of these changes did not remain until adulthood, the insufficient supply of proteins in early life altered the structure and functioning of the epididymis in important periods of postnatal development.